Perancangan Ulang Identitas Fariz Carwash Melalui Logo dan Pengaplikasiannya - Alghifary, Muhammad; Ekawardhani, Yully Ambarsih (Fakultas Desain Universitas Komputer Indonesia, 2024)
The redesign process to create and develop a new visual identity for Fariz Carwash, a vehicle washing service business, was carried out to ensure that the logo used is more conceptualized and reflects the company's line of work. The previous visual identity was not relevant to the company, with a logo that only consisted of hand visual elements and lacked balance. The method used in this redesign involved identifying issues with the current visual identity, developing a logo concept that reflects the business field, and applying the new logo technically across various media. This process included research into visual elements that can effectively and relevantly represent the business. In addressing this issue, a well-designed visual identity is crucial for building the company's image, enhancing competitiveness, and expanding consumer reach. A thoughtfully conceptualized visual identity is capable of conveying the core meaning of the company and enhancing its reputation in the public eye. The result of the redesign is a new visual identity for Fariz Carwash, including a logo redesign and a name change to better suit the services offered, becoming Fariz AutoMoto. A brand guideline and supporting media were also developed to accompany the logo, ensuring greater consistency for the company. A well-executed visual identity design process can positively impact the company's image and competitiveness in the market.